(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
Economic cooperation of the PRC with Central Asian countries has been developing successfully, however unforeseen difficulties have arisen in regional economic integration, this process is extremely slow. The perception by the countries of Central Asia of China, its image is one of the main reasons that impede the implementation of regional economic integration according to the Chinese scenario. Therefore, improving and enriching the image of China is the path that China should follow in strengthening relations with Central Asia, it is also an important factor in the creation of the Silk Road Economic Belt. The problems of forming the image of China have historical background and real reasons. China’s image must be shaped comprehensively and systematically, by improving its specific components in order to create a holistic and attractive image. The research article focuses on the current post-covid period image and perception of China in the Central Asian region including five states. The pandemic has had a very negative impact on the image of China in the region. Today, China faces one of the important tasks of correcting this situation. The post-crisis period is expected to strengthen the economic presence of the PRC in the region. Key words: China, Central Asia, BRI, pandemic, perspectives, perception